Implementasi Pola Misi Pengajaran Rasul Paulus Berdasarkan Roma 11:11-24 - Telaumbanua, Two Mei Lestari; Kurniawan, Martha Mulyani; Yuliani, Yuliani (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
This article examines the implementation of the Apostle Paul’s teaching-oriented mission pattern in Romans 11:11–24 and its relevance to missionary ministry among children, particularly those who have not yet come to know Jesus Christ as Lord and Savior. Through a theological approach, the study finds that Paul’s missionary strategy reveals the inexhaustible grace of God, wherein God provides salvation for all who are willing to believe and repent. Believers are commissioned by God to proclaim the salvation that has been accomplished by God Himself through and in Jesus Christ, and it is now the responsibility of believers to proclaim this salvation to those who have not yet believed.Due to the reality of human sin and total depravity, humanity is no longer capable of pursuing virtue; instead, human beings are wholly inclined toward sin, experience moral corruption, do not do good, and have become spiritually unprofitable. It is therefore evident that humanity is in need of the Gospel—that is, of God Himself as Savior—since only the power of God brings salvation to everyone who believes (Romans 1:16–17). Jesus Christ has become the reconciler and redeemer of humanity from sin, and everyone who believes in Him will receive eternal life in Christ Jesus.